The giant mechanical man [videorecording (DVD)] - Kirk, Lee; Fischer, Jenna, 1974-; Messina, Chris; Grace, Topher, 1978- (Distributed by New Video, 2012)
An unemployed thirty-something woman, with no direction in her life falls for a street performer.